2013
DOI: 10.1177/0194599813496374
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase Plasminogen Activator and Its Inhibitor Type‐1 as Prognostic Factors in Differentiated Thyroid Carcinoma Patients

Abstract: These findings indicate that high uPA and PAI-1 levels represent independent unfavorable prognostic factors in patients with differentiated thyroid carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
1
10
1
Order By: Relevance
“…Subsequent multivariate Cox regression analysis identified PAI-1 expression as one of the independent predictors of postsurgical survival of PDAC. These findings, which are largely consistent with those from other tumor types,[3233343536373839] suggested that PAI-1 might be a strong biomarker for long-term prognosis of PDAC. All our data support its promoting role in PDAC invasion.…”
Section: Discussionsupporting
confidence: 86%
“…Subsequent multivariate Cox regression analysis identified PAI-1 expression as one of the independent predictors of postsurgical survival of PDAC. These findings, which are largely consistent with those from other tumor types,[3233343536373839] suggested that PAI-1 might be a strong biomarker for long-term prognosis of PDAC. All our data support its promoting role in PDAC invasion.…”
Section: Discussionsupporting
confidence: 86%
“…The role of various components of Plasminogen activating system (PAS), especially urokinase-plasminogen activator (uPA) and plasminogen activator inhibitor type 1 (PAI-1), in thyroid cancer progression, metastasis, and prognosis and progression-free survival is established. Although significantly higher expression of uPA and PAI-1 ( 45 - 48 ), and uPA receptor ( 49 ) has been observed in malignant compared to benign, and in more aggressive compared to less aggressive thyroid cancers, its effect on hemostasis alteration has yet to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…There is a paucity of information on mechanisms involved in hemostatic changes in thyroid cancer and its subtypes and severities ( 29 , 39 , 43 , 45 - 49 ). Studies on changes in platelet adhesion and aggregation ( 29 ), various coagulation factors ( 39 ), components of PAS ( 45 - 49 ), endothelial functioning, and procoagulant molecules [e.g., tissue factor-positive micropeptides, cancer-derived tissue factor, cancer procoagulant, and heparanase ( 37 , 38 )] are required.…”
Section: Discussionmentioning
confidence: 99%
“…5 The utilisation of these two markers has been singularly successful in breast cancer, where the two markers are used linearly with definite cut-off points to identify early relapse and poor prognosis. 6,7,1115
Figure 2.Comparison of uPA/PAI-1 ratios for freeze-dried prostate tissue samples and the corresponding frozen samples from 25 patients presenting with PCa and BPH prostate abnormalities. Horizontal lines represent the mean uPA/PAI-1 ratio in each group of samples.
…”
Section: Resultsmentioning
confidence: 99%